RESULTS OF APPLICATION OF BUCCAL FAT PAD IN THE CLEFT PALATE SURGERY (World Bulletin of Public Health, 2024)
Currently, there is no accepted gold standard of surgical intervention for a specific type of cleft palate. Aspects of cleft surgery necessitate the development of new methods of palatoplasty with local tissues and the search for the optimal way to form flaps with sufficient size and good blood supply in order to avoid postoperative complications. The study is devoted to the analysis of the timing of epithelialization of sites in the area of lateral defects, depending on the material used to cover the wound surface. The results of the study of 103 patients demonstrated an acceleration of the healing and epithelialization process with the use of buccal fat pad (BFP) compared with iodoform, PRF and collagen sponge. The simplicity of mobilization, minimal traumatization and accessibility of the method determine the prospects of the proposed method for covering areas of lateral defects.